THE EFFECTIVENESS OF MANIPULATIVE MEDIA ON UNDERSTANDING THE CONCEPT OF MULTIPLING IN GRADE II MADRASAH IBTIDAIYAH - Syafira Nugroho; Linda Indiyarti Putri; Asma'ul Husna (IKIP Siliwangi, 2022)
The purpose of the study was to find out how effective the use of manipulative media was for understanding the multiplication concept of class II at MI Gisikdrono Semarang in 2020/2021. The design of this study used a quasi-experimental method with a pretest posttest control group design. The sample of this study was 23 students of class IIA as the experimental class and 27 students of class II B as the control class. Sample selection using simple random sampling technique. The results of statistical analysis show that by using manipulative media there is an effect on learning outcomes. This is evidenced by the results of the analysis of the N-gain score test which shows the average value of the experimental class of 0.68 or 68% which is included in the moderate or quite effective category. Furthermore, the acquisition of the count using the Paired Samples Statistics test stated that there was a difference in the average paired sample from the experimental class with the pretest of 59.13 < posttest 87.17, which means that there was a difference in the average results of the pretest and posttest of the experimental class. Through the results of this study, it is expected to be able to add insight to knowledge related to the importance of using manipulative media props.